Kontribusi Power Otot Tungkai pada Jauhnya Tendangan (Long Passing) dalam Permainan Sepakbola - Muhammad Jawahiril Arzaq; Abdul Aziz Hakim (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study was conducted with the aim of determining the contribution of leg muscle power to long passing in football games at SSB Margosuko Tuban. The type of research applied in the research to be carried out refers to quantitative descriptive research. The subjects in this study involved 15 players. Data collection techniques used observation and tests, the tests used were power tests applied with vertical jump tests and ball kicking tests. Data analysis techniques applied normality tests and hypothesis tests with Pearson correlation test analysis. The results of this study indicate that there is a contribution between leg muscle power to the distance of kicks in football games, this condition is indicated by the person correlation value of 0.639, so it can be concluded that leg muscle power contributes to the distance of kicks (long passing) in football games, especially for SSB Margosuko Tuban players.